USE OF THE SURROUNDING ENVIRONMENT AS A LEARNING RESOURCE IN LEARNING SCIENCE IN CLASS IV SDIT ULUMUDDIN LHOKSEUMAWE - Raudhatul Muna; Siti Mayang Sari (SENSEI RESEARCH CENTER, 2024)
The aim of this research is to determine students' learning difficulties and their In the learning process, it is of course important to involve students in exploration, so that understanding of concepts and basic understanding of knowledge, especially science, can be understood by students easily. Learning resources can be found in the child's surroundings. The life of flora and fauna and social conditions are very interesting to observe and talk about, which is information and a source of learning for children about the environment. The aim of this research is to find out how the learning process works by utilizing the school environment as a learning resource in science subjects in class IV SDIT Ulumuddin, and to find out the role and obstacles that hinder the process of using the school environment as a learning resource in science subjects in class IV SDIT Ulumuddin.